The Vedanta Dindimah = Drum-beats of Vedānta : with a supplement of Kāśmir Śaiva & Vedānta Puruṣa - Nr̥siṃhāśrama.; Śaṅkarācārya; Kaula, Jānakīnātha, 1914- (Srinagar, Kashmir : Utpal Publication, 1990)
Treatise of the Vedanta philosophy.
Variously attributed to Śaṅkarācārya and Nr̥siṃhāśrama.
English and Sanskrit.
Includes bibliographical references.
Mode of access: Internet.
Keywords: Vedanta -- Early works to 1800.